KEAWETAN BATANG AREN (Arenga pinnata Merr.) - Ginuk Sumarni; Agus Ismanto; Mohammad Muslich (Jurnal Penelitian Hasil Hutan, 2003)
Aren (Arenga pinnata Merr ) is one  of the natural resources of the  tropics  which has been used widely in  the daily life of the  local community  as a sustainable resource due to its wide distribution, high availability, and desirable properties. The significant uses  in  Indonesia  are for building material,  making various baskets, roof, sugar,  candied fruits, and handicraft.The specimen of aren was selected from Jasinga, West Java. A log sample was taken from three height levels of the stem, viz top,  middle and bottom sections. Each section was tested to the  dry wood termite Cryptotcrmes cynoccphalus Light.,  the subterranean  termite Coptotcrmes  curvignathus,  Holmgren the  powder post  beetle and  Heterobostrychus aequalis Wat the fungi  Schyzophyllum commune Fr.,  Pycnoporus sanguincus  (Fr.) Karst, and the Dacryopinax  spathularia (Schw.)  MarstThe results showed that aren stem specimens taken from  the top,  middle and bottom sections are resistant  to dry  wood termite (Cryptotcrmes  cynocephalus  Light.),  especially the bottom section which can be classified as durability class I.  The results also showed  that aren stem is resistant to powder post beetle (Heterobostrychus aequalis Wat.) and fungi (Schyzophyllum commune Fr., Pycnoporus sanguincus (Fr.) Karst. and Dacryopinax   spathularia  (Schw.) Marst.).  On the other hand,  aren stem is not resistant   to the  subterranean   termite Coptotermes curvignathus Holmgren,  especially  the top section which can be classified  as durability class V.